Thermomechanical fatigue of heat-resistant austenitic cast iron EN-GJSA-XNiSiCr35-5-2 (Ni-Resist D-5S). (June 2017) - Kühn, Hans-Joachim; Rehmer, Birgit; Skrotzki, Birgit
Highlights: The IP and OP TMF behavior of EN-GJSA-XNiSiCr35-5-2 was characterized. The differences in fatigue life between the two phase angles are small. The IP test with Tmax  = 900 °C behaves differently from all other testing conditions. The reason is intergranular creep damage with wedge-type cracks. Abstract: TMF tests were carried out on EN-GJSA-XNiSiCr35-5-2 at constant minimum temperature (400 °C) and varying maximum temperatures ( Tmax  = 700 °C, 800 °C, 900 °C) with hold times of 180 s at Tmax and two phase angles (in-phase (IP), 180° out-of-phase (OP)). The results showed a comparable strength under OP- and IP-TMF loading. At Tmax  = 700 °C and 900 °C, the lifetime in IP-tests was slightly longer than that of OP-tests, while it is vice versa at Tmax  = 800 °C. The IP-tests at Tmax  = 900 °C showed a similar lifetime as OP-tests at Tmax  = 700 °C and 800 °C, which was unexpected for such a high testing temperature. All IP-tests at Tmax  = 900 °C showed a continuous cyclic softening from the beginning on, which was different from all other testing conditions. Complementary metallographic investigations indicated that under this test condition, intergranular creep damage is present in the volume of the test pieces.